Practical Strategies for The Economic Development of Mexico: Nearshoring Trend - Santillán Luna, Ignacio; Ceja Pizano, J. Jesús; Pineda Domínguez, Daniel (Mercados y Negocios, 2024)
This research aimed to suggest practical strategies for Mexico’s economic development through the trend of nearshoring. It involved identifying, analyzing, and organizing the causes of the conflict between China and the USA over international trade and exploring the opportunities that nearshoring to Mexico can offer. Qualitative research methods were applied, and documentary research techniques were used based on two study objects: a) the Sino-American dispute over international trade and b) nearshoring to Mexico. Nearshoring to Mexico is driven by various factors, including tariff benefits from Free Trade Agreements, low labor costs in manufacturing companies, and a stable exchange rate. Therefore, Mexico needs to encourage the development of industrial parks, implement an effective Public Security Policy, offer tax incentives to attract Foreign Direct Investment and improve port, road, and air infrastructure to take full advantage of this trend.